Hasil Pra-Pengabdian Tentang Zakat Untuk Pembangunan Ekonomi Yang Adil dan Sejahtera: Anisis Zakat Wilayah Jawa Tengah - Fadhilah, Utami Nur; Khasanah, Rizky Uzwatun; Khikmah, Astri Afifatul; Agustin, Nur Adinda Eliana; Darutama, Ardiyan (Dharmahita: Journal of Community Service and Development, 2025)
Zakat is one of the pillars of Islam that plays an important role in improving community welfare and reducing economic inequality. This pre-service study aims to explore the potential of zakat in Central Java and the challenges faced in its management. Using a descriptive and qualitative approach, this study collects data from various literature sources to analyze the role of zakat in the socio-economic context. The method used is an in-depth literature review, focusing on the collection, assessment, and synthesis of information related to zakat. This pre-service study aims to provide a better understanding of the function of zakat in creating a fair and prosperous economy, as well as to identify the challenges faced in the distribution of zakat. The results show that the potential of zakat in Central Java is enormous, with an estimated value of Rp3.1 trillion per year. However, there are significant challenges, such as low public understanding of zakat, lack of transparency in management, and limited human resources. To overcome these challenges, strategies are needed to strengthen BAZNAS through education, digitalization, and the development of innovative economic empowerment programs. Thus, this pre-service program is expected to make a meaningful contribution to understanding and optimizing zakat management in Central Java, as well as encouraging community participation in fulfilling their zakat obligations for the common good